A series of diabetic ketoacidosis associated with the use of sodium-glucose co-transporter-2 inhibitors in secondary care. Issue 12 (December 2022) - Taverner, Sofia; Eng, Cindy; Watson, Rebecca; George, Siba; Edwards, Amanda; Williams, David M.; Stephens, Jeffrey W.
Abstract: Background and aims: Sodium-glucose co-transporter-2 inhibitors (SGLT-2i) are associated with diabetic ketoacidosis (DKA), however limited case series are published. Methods: We evaluated the characteristics of patients admitted with SGLT-2i associated DKA. Results: Over 4 months, 22 patients were identified; 45.5% of DKA was not associated with concurrent illness. Conclusion: DKA is not uncommonly associated with SGLT2i with no clear patient factors associated with severity. Highlights: Sodium-glucose co-transporter-2 inhibitor (SGLT-2i) associated DKA was observed in 22 patients over 4-months. No differences in age, diabetes duration, HbA1c or admission biochemistry were seen in those with concurrent illness. Our results observed no clear association between patient characteristics or co-morbidity and SGLT-2i-associated DKA.